The Use of Fisheye Views for Displaying Semantic Relationships in a Medical Taxonomy - Komorowski, Henryk Jan (1987)
One of the critical issues for the development of a Unified Medical Language System (UMLS), or taxonomy of medical terms, is the identification of semantic features and relationships which should be represented in the UMLS, and the design of the appropriate structure for storing and displaying these features and relationships. A particular focus of our research is the development of software tools to facilitate the authoring, maintaining, and viewing of taxonomic relationships. One approach is the use of the “fisheye view” for displaying a region of interest in a semantic network.